If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 3c = 38 + -1c Solving 6 + 3c = 38 + -1c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add 'c' to each side of the equation. 6 + 3c + c = 38 + -1c + c Combine like terms: 3c + c = 4c 6 + 4c = 38 + -1c + c Combine like terms: -1c + c = 0 6 + 4c = 38 + 0 6 + 4c = 38 Add '-6' to each side of the equation. 6 + -6 + 4c = 38 + -6 Combine like terms: 6 + -6 = 0 0 + 4c = 38 + -6 4c = 38 + -6 Combine like terms: 38 + -6 = 32 4c = 32 Divide each side by '4'. c = 8 Simplifying c = 8
| 7x+3=6x+26 | | f(x)=5x^3+15x^2-120x | | 5x+5-6x=2x+17-7x | | 35x(25+40)=700 | | 9y+7=31+y | | y-2=-3(x-5) | | 100+80t+4b= | | 34.7x+40.9+38.8x+18.8= | | 4x+6-2x=2(x-3) | | -4x^2-12x-10=0 | | x(x+4)=-84 | | 7x^2-36x+6=0 | | 3x(x-1)+15=7 | | 40+2y-16=11y-11-4y | | 1223423123x=213123123 | | -3x+18=-10x+4 | | 3x+9=5x-19 | | 6(2.5)+3y=12 | | (3x)(3x-2)(x)=540 | | 0=0.3x^2+2x-50 | | x-55=10 | | 2q^3-5q^2-500=0 | | 42-n*n=n | | 1996+43x=0 | | log(10)x+log(10)x-1=log(10)30 | | -24+11=5x+3-4x | | .10(c+3)=-12 | | log(x)+log(x-1)=log(30) | | 21-x=28 | | n-n*n=72 | | 4(a+9)=7[a-(3-a)] | | 9x^2=50x-25 |